Conditional reflex to urine culture: Evaluation of a diagnostic stewardship intervention within the Veterans' Affairs and Centers for Disease Control and Prevention Practice-Based Research Network. (25th February 2021) - Claeys, Kimberly C.; Zhan, Min; Pineles, Lisa; Lydecker, Alison; Clore, Gosia; Goto, Michihiko; Leekha, Surbhi; Linkin, Darren; Evans, Charlesnika T.; Trautner, Barbara W.; Goetz, Matthew B.; Baghdadi, Jonathan D.; et al.
Abstract: Objective: In the absence of pyuria, positive urine cultures are unlikely to represent infection. Conditional urine reflex culture policies have the potential to limit unnecessary urine culturing. We evaluated the impact of this diagnostic stewardship intervention. Design: We conducted a retrospective, quasi-experimental (nonrandomized) study, with interrupted time series, from August 2013 to January 2018 to examine rates of urine cultures before versus after the policy intervention. We compared 3 intervention sites to 3 control sites in an aggregated series using segmented negative binomial regression. Setting: The study included 6 acute-care hospitals within the Veterans' Health Administration across the United States. Participants: Adult patients with at least 1 urinalysis ordered during acute-care admission, excluding pregnant patients or those undergoing urological procedures, were included. Methods: At the intervention sites, urine cultures were performed if a preceding urinalysis met prespecified criteria. No such restrictions occurred at the control sites. The primary outcome was the rate of urine cultures performed per 1, 000 patient days. The safety outcome was the rate of gram-negative bloodstream infection per 1, 000 patient days. Results: The study included 224, 573 urine cultures from 50, 901 admissions in 24, 759 unique patients. Among the intervention sites, the overall average number of urine cultures performed did not significantly decrease relative to the preintervention period (5.9% decrease; P = 0.8) but did decrease by 21% relative to control sites ( P < .01). We detected no significant difference in the rates of gram-negative bloodstream infection among intervention or control sites ( P = .49). Conclusions: Conditional urine reflex culture policies were associated with a decrease in urine culturing without a change in the incidence of gram-negative bloodstream infection.